A natureza e o homem: categorias a considerar no pensamento de Feuerbach - de Sousa, Maria Celeste; Cabral, João Robson (Kairós: Revista Acadêmica da Prainha, 2021)
Feuerbach’s line of thought regarding Christianityis presented dissociated from divinity. The philosopher develops from the work The Essence of Christianity a criticism towards theology and a philosophical, anthropological and genetic-physiological discussion regarding religions, overall, but more directed to Christianity, the author’s birth religion and his object of investigation. Feuerbach is a defender of the autonomous nature, without a Creator, everything known by a religious man about God runs through human culture, namely, it is elaboration of the human spirit attributed to divinity. Whatever it is manifested to man is not God, but the man’s self-consciousness endowed with rational and emotional capabilities. The link to divinity emerges only as fantasy and man’s self-projection.